(untitled) - Ng, Yew-Kwang (London, 1979)
The book covers not only the basic topics in welfare economics at an introductory level but also advanced and new arguments. It begins with a treatment of Pareto optimality and welfare criteria anf continues with a systematic analysis of such topics as consumer supplus and social choice, externality and public goods. In addition, the book considers more advanced issues, including the distinction between welfare and preference, between basic value judgements and subjective judgements of fact, and discusses such new argument as the concept of 'conscience effects' in externalities and 'new theory of the third best'. The book concludes with a call for a complete and interdisciplinary study of welfare or happiness.
Keywords: Welfare economics